SISTEM INFORMASI PENDAPATAN JASA PADA KOPERASI PDAM TIRTA PATRIOT BEKASI - Yuni Eka Achyani; Eni Arviana (JURNAL TEKNIK KOMPUTER AMIK BSI, 2018)
Development of information technology is increasingly rapidly makes the need for information is increasing. Information is very important in supporting the course of a company to achieve the desired goal. With the data processing program, and the information will be more rapid, precise and accurate in its presentation. Employees Cooperative PDAM Tirta Patriot is a business entity that is engaged in trade and services. By using the Web program can perform inputting and storing data quickly and can be easier to find the data that we want, so as to reduce the mistakes that often occur. The data collection method used by the authors is the direct observation, interviews, and literature. The author's purpose of research on web-based revenue service information system on Employee Cooperation Tirta Patriot PDAM in the hope to overcome the obstacles that have occurred in the system of service revenue manually, and can assist in making reports service revenue.